Lumberjanes. 4, Out of time - Stevenson, Noelle; Watters, Shannon (Boom! Box, 2016)
When a blizzard hits the camp where the Lumberjanes are staying, a mysterious taxidermist shows up to save the day. Separated from the group, Jen must find her way back to the other girls.